ROS 2016
DOI: 10.20455/ros.2016.865
|View full text |Cite
|
Sign up to set email alerts
|

MitoSOX-Based Flow Cytometry for Detecting Mitochondrial ROS

Abstract: MitoSOX-based assays are widely used to detect mitochondrial reactive oxygen species (ROS), especially superoxide. To this end, 5 μM MitoSOX is commonly used. In this ROS Protocols article, we described the flow cytometric protocol involving the use of various concentrations of MitoSOX (1, 2.5, 5 μM) for detecting mitochondrial ROS in control and mitochondrial DNA-deficient (MD) melanoma B16-F10 cells. We also compared the MitoSOX-based flow cytometry with lucigenin-derived chemiluminometry for their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 10 publications
1
131
0
1
Order By: Relevance
“…As shown in Figure 1, doxorubicin exhibits characteristic fluorescence spectra of excitation and emission with maximum excitation (λex) and emission (λem) wavelengths being 470 and 560 nm, respectively. Notably, the λex and λem are very similar to those of ROS-oxidized MitoSOX [7]. This observation has important implications in using MitoSOX assays to detect the ROS formation induced by doxorubicin.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figure 1, doxorubicin exhibits characteristic fluorescence spectra of excitation and emission with maximum excitation (λex) and emission (λem) wavelengths being 470 and 560 nm, respectively. Notably, the λex and λem are very similar to those of ROS-oxidized MitoSOX [7]. This observation has important implications in using MitoSOX assays to detect the ROS formation induced by doxorubicin.…”
Section: Resultsmentioning
confidence: 96%
“…During our studies on MitoSOX-based fluorescence assays, we observed that doxorubicin has similar fluorescence spectrometric properties to MitoSOX, a probe for detecting reactive oxygen species (ROS), especially superoxide [7]. We thus further characterized the fluorescence properties of doxorubicin in a hope to develop fluorescence-based assays for detecting this commonly used anticancer drug in biological systems.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were washed and stained with Hoechst 33342 stain for 10 minutes at room temperature. For flow cytometry, cells were labeled with dye at 1 µM final concentration, incubated in the dark at 37°C and immediately loaded for ROS fluorescence detection in the FL-2 channel using flow cytometry (Kauffman et al, 2016).…”
Section: Mitochondrial Ros Measurementmentioning
confidence: 99%
“…Depending on the experiment, cells were either collected immediately for analysis or challenged with H2O2 for an additional 30 minutes prior to collection. Mitochondrial •O2levels were determined with the fluorescent dye, MitoSox Red (Invitrogen), according to an established protocol (Kauffman et al, 2016). Briefly, cells were incubated in fresh media for 4 hours, washed with PBS, and incubated in 1mL of 5µM MitoSOX Red in HBSS (Gibco) for 20 minutes.…”
Section: Flow Cytometry Analyses Of Rosmentioning
confidence: 99%